MSME Strategy for International Market: A Case Study of Fruit and Vegetable Chips in Batu, East Java, Indonesia - Novianto, Abdullah Syakur; Sudarmiatin, Sudarmiatin (Cita konsultindo, 2024)
This study aims to describe the internationalization strategy of MSMEs and identify the strengths, weaknesses, opportunities, and threats of the internationalization process of export-oriented fruit and vegetable chips MSMEs at CV Arjuna 999 Batu. The approach used in this study is qualitative. This study is a SWOT analysis with an internal and external matrix (IFAS & EFAS) of one MSME, which is a key informant for fruit and vegetable chip exporters in Batu. The study results indicate that CV Arjuna 999 fruit and vegetable chips have a good level of success. Based on the results of the IFAS-EFAS analysis, the position is in quadrant VI, namely the cautious phase. The strategies that can be used to improve the internationalization process are expanding market segments with online and offline methods, increasing online marketing networks, creating other products or variants, diversifying products, expanding the role of associations, improving technological skills, lobbying policies to local governments, adapting to changes in consumer behavior, implementing cooperation with associations, and optimizing promotions through various media.